Spatio-temporal analysis of urban changes and surface water quality - Carstens, Dana; Amer, Reda (Journal of hydrology (Amsterdam), 2019)
•Remote sensing and GIS enables monitoring and management of water quality.•Land cover are causing changes in water quality over temporal and spatial scales.•A positive correlation was found between water quality deterioration and urban expansion.•Levels of fecal coliform were consistent with increased urbanization in water bodies.•A GIS model to handle and reduce the processing time of water quality large datasets. The combination of remote sensing techniques and Geographic Information Systems (GIS) to measure water quality allows researchers to monitor changes in various water quality parameters over temporal and spatial scales that are not always readily apparent from in situ measurements. This study involves using Landsat images and in situ data within GIS to map urban expansion and its resulting influences on water quality in the Pontchartrain Basin over the last three decades. The Pontchartrain Basin is located in southeast Louisiana and covers an area of 25,000 km2 that encompasses sixteen parishes east of the Mississippi River and four Mississippi Counties. A Landsat Thematic Mapper (TM) image from 1985 and a Landsat Operational Land Imager (OLI) image from 2015 were processed using the Spectral Angle Mapper (SAM) algorithm to map urban expansion. In order to estimate how water quality has changed in the Pontchartrain Basin between 1985 and 2015, in situ water quality data from the Louisiana Department of Environmental Quality was interpolated using Empirical Bayesian Kriging (EBK). Comparing urban expansion produced from SAM classification with urban indices, impervious surfaces were better identified and distinguished from other land cover features. The results of this study demonstrated that high levels of fecal coliform were consistent with increased urbanization in water bodies in the Pontchartrain Basin. Phosphorous levels were higher in 2015 compared to 1985 and were at levels high enough to lead to eutrophic conditions. Dissolved oxygen levels were lower near the mouth of the Mississippi river in 2015 than in 1985. The results indicated that urbanization has negative impact on water quality. The geospatial model is recommended to effectively manage and reduce the processing time of large water quality datasets.